Peran Pendidikan Inklusi Dalam Perspektif Pendidikan Islam - Putri Zahara; Adinda Dwi Putri; Fitria Nurkarimah; Wismanto Wismanto; Muhammad Fadhly (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
As stated in Article 4 of the Preamble to UUD 4445 of 1945, achieving quality education is one of the goals of the Indonesian nation. Apart from that, education is also a very important element for the development of civilization. Improving the quality of education. The purpose of writing this article is to reveal the role of Islamic inclusive education and Islamic education. Islamic and Western theoretical collaborators agree that inclusive education is consistent with Islamic teachings and values. This is because Islamic teachings themselves require obligations and opportunities in seeking knowledge, and do not discriminate between differences in ethnicity, skin color, flag, skin color, etc., as well as differences in human physical conditions. it requires careful attention. When writing this article, the author used a research library-based research method, or it could also be called library research. This literature includes research, such as the use of media to collect library materials, books, journals and articles that can support this study in solving problems. The method is to collect library materials and then analyze the different materials found according to the questions asked. The results of this research show that the existence of inclusive education, both in Islamic educational institutions and in various other communities, supports children with special needs and creates creative conditions and environments that do not discriminate between normal children and children with special needs.